Love and grumpiness - Berrios, Frank; Laberis, Steph (New York Random House, 2019)
"Valentine's Day is all about love and friendship--things Grumpy Cat hates! But when she notices Pokey enjoying sweet treats and kind wishes, she just might change her grumpy ways"--Amazon.com
"Valentines! Stickers! Poster!"--Cover.
108075
Keywords: Grumpy Cat -- Juvenile fiction; Valentine's Day -- Juvenile fiction; Fiction; Juvenile works